C-reactive protein: a sensitive marker in the management of treatment response in parapneumonic empyema of children - Dilber, Embiya; Çakır, Murat; Kalyoncu, Mukaddes; Ökten, Ayşenur (The Turkish Journal of Pediatrics, 2003)
C-reactive protein (CRP) is one of the best indicators of the acute phase response to inflammation. The rapid kinetics of CRP metabolism appears to closely parallel the degree of inflammation. The purpose of this prospective study was to analyze the clinical value of CRP, erythrocyte sedimentation rate (ESR), and white blood cell count (WBC) in the assessment response to treatment in children with parapneumonic empyema. Thirty-eight children were prospectively studied. CRP was elevated in all patients on the day of hospital admission. With antibiotic treatment, serum CRP levels fell rapidly within the first days, and in 32 patients who had uncomplicated course, serial CRP levels fell progressively at each measurement. All but four patients had normal CRP levels on the day of hospital discharge. ESR was also elevated in all patients on the day of hospital admission. Despite antibiotic treatment, ESR continued to increase in all patients in the first few days, with peak values reached on day 3. Only three patients had normal ESR levels on the day of hospital discharge. In six patients who had a complicated course, after an initial decrease, CRP levels began to rise earlier than ESR and WBC count. Plasma CRP level is a sensitive marker not only in the diagnosis of parapneumonic empyema, but also in the management of treatment response.